Assembly of dicobalt and cobalt–aluminum oxide clusters on metal–organic framework and nanocast silica supports. (20th June 2017) - Desai, Sai Puneet; Malonzo, Camille D.; Webber, Thomas; Duan, Jiaxin; Thompson, Anthony B.; Tereniak, Stephen J.; DeStefano, Matthew R.; Buru, Cassandra T.; Li, Zhanyong; Penn, R. Lee; Farha, Omar K.; Hupp, Joseph T.; et al.
Abstract : NU-1000, a mesoporous metal–organic framework (MOF) featuring hexazirconium oxide nodes and 3 nm wide channels, was infiltrated with a reactive dicobalt complex to install dicobalt active sites onto the MOF nodes. The anchoring of the dicobalt complex onto NU-1000 occurred with a nearly ideal stoichiometry of one bimetallic complex per node and with the cobalt evenly distributed throughout the MOF particle. To access thermally robust multimetallic sites on an all-inorganic support, the modified NU-1000 materials containing either the dicobalt complex, or an analogous cobalt–aluminum species, were nanocast with silica. The resulting materials feature Co2 or Co–Al bimetallated hexazirconium oxide clusters within a silica matrix. The cobalt-containing materials are competent catalysts for the selective oxidation of benzyl alcohol to benzaldehyde. Catalytic activity depends on the number of cobalt ions per node, but does not vary significantly between the NU-1000 and silica supports. Hence, the multimetallic oxide clusters remain site-isolated and substrate-accessible within the nanocast materials.